2021
DOI: 10.1111/cas.14789
|View full text |Cite
|
Sign up to set email alerts
|

Discoidin domain receptors orchestrate cancer progression: A focus on cancer therapies

Abstract: Discoidin domain receptors (DDR), including DDR1 and DDR2, are special types of the transmembrane receptor tyrosine kinase superfamily. DDR are activated by binding to the triple‐helical collagen and, in turn, DDR can activate signal transduction pathways that regulate cell‐collagen interactions involved in multiple physiological and pathological processes such as cell proliferation, migration, apoptosis, and cytokine secretion. Recently, DDR have been found to contribute to various diseases, including cancer.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 68 publications
(155 reference statements)
2
29
0
Order By: Relevance
“…Moreover, we demonstrated that DDR1 promotes thyroid cancer cell dedifferentiation and the acquisition of a stemlike phenotype by enhancing the IGF-2/IR-A autocrine signaling loop [9,10] and plays a critical role in promoting bladder cancer cell motility by linking the IGF1R and IR-A to the regulation of F-actin cytoskeleton dynamics [15]. Collectively, these data uncover novel, non-canonical DDR1 functions, which strongly support the pro-tumorigenic and pro-metastatic role of DDR1 [16][17][18].…”
Section: Introductionsupporting
confidence: 60%
“…Moreover, we demonstrated that DDR1 promotes thyroid cancer cell dedifferentiation and the acquisition of a stemlike phenotype by enhancing the IGF-2/IR-A autocrine signaling loop [9,10] and plays a critical role in promoting bladder cancer cell motility by linking the IGF1R and IR-A to the regulation of F-actin cytoskeleton dynamics [15]. Collectively, these data uncover novel, non-canonical DDR1 functions, which strongly support the pro-tumorigenic and pro-metastatic role of DDR1 [16][17][18].…”
Section: Introductionsupporting
confidence: 60%
“…DDR1 and DDR2 function as ECM signal transducers, binding to the ECM collagen, and initiating intra-cellular signaling ( Henriet et al, 2018 ). DDRs and their signaling pathways are promising targets for the development of new clinical treatments, particularly in cancers with altered DDR expression or function ( Gao et al, 2021 ).…”
Section: Discoidin Domain Receptor Tyrosine Kinasesmentioning
confidence: 99%
“…Interestingly, many DDR signaling pathways (including IGF-DDR) can be used to treat chronic inflammatory diseases, including cancer ( Vella et al, 2019 ). While we have focused here on DDR1 and DDR2 in breast and ovarian cancer, they are increasingly important and relevant anti-cancer targets for multiple tumor types ( Lafitte et al, 2020 ; Bhanumathy et al, 2021 ; Gao et al, 2021 ). Previously Merestinib (LY2801653; inhibiting DDR1/2 and MET, MST1R, FLT3, AXL, MERTK, TEK, ROS1, and MKNK1/2) has shown potent anti-tumor activity in clinical trials against multiple advanced cancers ( Yan et al, 2013 ).…”
Section: Clinical Developments Of Discoidin Domain Receptor Tyrosine Kinase 1 and Discoidin Domain Receptor Tyrosine Kinase 2 Targeted Thmentioning
confidence: 99%
“…DDR are activated by binding to the collagen and can activate signal transduction pathways. At the same time, DDR can regulate cell-collagen interactions which involved in multiple processes such as cell proliferation, migration, and apoptosis ( Gao et al, 2021 ). Moreover, the IIGFs-DDR1 crosstalk is considered the major mediator of therapy resistance of cancer cells ( Buck et al, 2010 ; Vella et al, 2019 ).…”
Section: Microenvironment and Cam-drmentioning
confidence: 99%